Capitalism and the sea: Sovereignty, territory and appropriation in the global ocean. (August 2018) - Campling, Liam; Colás, Alejandro
This paper introduces the term 'terraqueous territoriality' to analyse a particular relationship between capitalism as a social formation, and the sea as a natural force. It focuses on three spaces – exclusive economic zones, the system of 'flags of convenience' and multilateral counter-piracy initiatives – as instances of capitalist states and firms seeking to transcend the geo-physical difference between firm land and fluid sea. Capital accumulation, it is argued here, seeks to territorialise the sea through forms of sovereignty and modes of appropriation drawn from experiences on land, but in doing so encounters particular tensions thereby generating distinctive spatial effects. By exploring the articulation between sovereignty, territory and appropriation in the organisation of spaces where land meets sea, the article seeks to demonstrate the value of an analytical framework that underlines the terraqueous nature of contemporary capitalism.